Broadcast Media Framing of a Middle East Political Rift - King, John Mark; King, Meruyert Bakenova (Journal of Marketing Development and Competitiveness, 2021)
A random sample of transcripts of 393 broadcast news headlines about a political rift between Qatar and Saudi Arabia, Egypt, the United Arab Emirates and Bahrain were analyzed. Analysis included headlines from 11 broadcast networks in Malaysia, Canada, the United Kingdom and the United States. The timeframe was June 5, 2017, the day the four Arab nations simultaneously cut off diplomatic relations with Qatar, until Oct. 23, 2018. Tone toward Qatar was 79.1% negative, 9.4% positive and 11.5% neutral. Headlines broadcast in the United Kingdom (85.7%) were the most frequently negative in tone; headlines broadcast in Malaysia were the least frequently negative in tone (66.0%). Overall tone toward Qatar shifted from being more frequently negative (82.1%) to more frequently neutral (17.2%) or positive (41.4%) after the midpoint of the timeframe. The most frequent topics were the demands the four Arab nations required to restore diplomatic relations with Qatar (14.0%), United States President Donald Trump criticizing Qatar (9.9%) and headlines about Qatar not being a democratic nation (8.4%).